Rethinking and Moving Beyond GDP : A New Measure of Sarawak Economy Panorama - Ling, Shirly Wong Siew; Hao, Tan Toh; Shazali, Abu Mansor; Liew, Venus Khim-Sen (Canadian Center of Science and Education, 2018)
Despite the relatively strong adjustment in the global economy outlook, the Malaysian economy remains uncertain as the ringgit movement lies ambiguously ahead while volatile capital flows, inflationary pressure, and the vulnerable external sector and global trade remain intense. The Sarawak economy, which relies heavily on primary commodities and export earnings from oil-based industries, will soon face a noxious mixture of economic risks following the decrease in commodity prices. Thus, it is essential to develop a well-timed signaling mechanism to estimate the unpredictable economic forces that develop from the complex and multidimensional issues of domestic and global economies. The ideology of indicator construction from the Conference Board will be applied in this study to build a composite leading indicator, called the Sarawak Business Cycle Indicator (SBCI), to trace the cyclical movement of the aggregate economic activity in Sarawak. In this respect, the SBCI, which has demonstrated statistical significance with an average leading power of 3.5 months, is expected to be important in reflecting a notable economic outlook for the State. More importantly, the SBCI will serve as a valuable reference to act as a short-term forecasting tool to provide insight at both the national and state levels.